2016
DOI: 10.1007/s41230-016-6036-4
|View full text |Cite
|
Sign up to set email alerts
|

Separation of primary Si and impurity boron removal from Al-30%Si-10%Sn melt under a traveling magnetic field

Abstract: C rystalline silicon is one of the materials used for solar cells, accounting for over 90% of the photovoltaic (PV) materials [1] . However, the PV industry has to face a serious low-cost feedstock supply shortage due to a rapid expansion of the solar cell industry. To lower the production cost of Si solar cells, a promising way is to upgrade metallurgical-grade silicon (MGSi) to solar-grade silicon (SoG-Si) with metallurgical treatments [2][3][4][5] . However, boron (B) element, an impurity in MG-Si, cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…The currently observed Si separation in specimens, without stirring, supports findings regarding the important role of the occurring temperature gradient [88][89][90], whereas Si reduction under RMF seems to result from secondary azimuthal flow and the Si crystal movement. The occurrence of a purely eutectic center in the current study agrees with the majority of the before mentioned studies; however, it contradicts [73], where Si crystals were also observed in the center.…”
Section: Reduction Of Si Crystalssupporting
confidence: 84%
See 2 more Smart Citations
“…The currently observed Si separation in specimens, without stirring, supports findings regarding the important role of the occurring temperature gradient [88][89][90], whereas Si reduction under RMF seems to result from secondary azimuthal flow and the Si crystal movement. The occurrence of a purely eutectic center in the current study agrees with the majority of the before mentioned studies; however, it contradicts [73], where Si crystals were also observed in the center.…”
Section: Reduction Of Si Crystalssupporting
confidence: 84%
“…The occurrence of a purely eutectic center in the current study agrees with the majority of the before mentioned studies; however, it contradicts [73], where Si crystals were also observed in the center. In the current study, the observed reduction in Si crystals may come from flows reducing the temperature gradient in the melt throughout the sample, and as presented in [88][89][90], the gradient appears to be important. The effects of the temperature gradients, cooling rate and strength of magnetic field require more investigations.…”
Section: Reduction Of Si Crystalsmentioning
confidence: 48%
See 1 more Smart Citation
“…The microstructure of hypoeutectic Al-Si casting alloys consists of the primary α-Al and the Al-Si eutectic which influence on the mechanical properties of the alloy [2]. Xugang et al [3] reported that the plate-like eutectic Si phase of the ascast hypoeutectic Al-Si alloy resulted in deleterious effect on mechanical properties. Alternatively, fine fibrous eutectic Si was found to improve mechanical properties of the Al-Si alloy, especially the ductility [4].…”
Section: Introductionmentioning
confidence: 99%